Vol. 683 : Multifunctional Materials: Development and Application: The XII International Conference "Prospects of Fundamental Sciences Development" (PFSD-2015), April 21-24, 2015, Tomsk, Russia; [proceedings]; Key Engineering Materials - Kurzina I. A. Irina Aleksandrovna; Godymchuk (Godimchuk) A. Yu. Anna Yuryevna (2016, 2016)
Title screen